Ureteral duplication with intrasinusal ureteral junction and epididymal ureteric ectopia - Venugopalan, A V; Shanmughadas, K V; Gupta, Piyush; Cardoza, Felix (Indian Journal of Case Reports, 2018)
We report a case of 47-year-old adult male who presented with episodic unilateral scrotal swelling associated with dragging pain,with a history of spontaneous resolution and associated non-colicky right flank pain. On evaluation, he was diagnosed to haveureteral duplication with intrasinusal ureteral junction and epididymal ureteral ectopia. Treatment included laparoscopic right lowerpole nephrectomy for the thinned out draining segment with ectopic ureterectomy. In literature, very few cases of ureteral duplicationin an inverted Y have been reported. In such cases, epididymal ureteral ectopia has been found to be extremely rare. Here, in thiscase, uncharacteristic symptoms mimicking chronic epididymo-orchitis, diagnostic difficulties and findings are described.